دور الأدوات الإحصائية لإدارة الجودة الشاملة في تحسين الأداء دراسة ميدانية على الشركة العامة للخيوط القطنية في محافظة اللاذقية - دخول غسان (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يتناول هذا البحث دراسة دور أدوات إدارة الجودة الشاملة، كمدخل لتحسين الأداء في الشركة العامة للخيوط القطنية في محافظة اللاذقية. حيث تم دراسة الأدوات الإحصائية لإدارة الجودة الشاملة، ودورها في تحسين الأداء وتخفيض التكاليف. وتم اعتماد المنهج الوصفي التحليلي. وتم استخدام نموذج الارتباط ونموذج الانحدار البسيط لدراسة العلاقة بين كل من المتغيرين التابعين والمتغير المستقل. وقد توصل البحث إلى: إن قيمة معامل الارتباط بين الأدوات الإحصائية لإدارة الجودة الشاملة وتحسين الأداء هي (0.949)، وهذا يدل على وجود درجة ارتباط قوية بين المتغيرين. وإلى أنَّ التغيرات الحاصلة من استخدام الأدوات الإحصائية لإدارة الجودة الشاملة تؤدي إلى تغير بنسبة (90.1%) في مجال استخدامها لتحسين الأداء في الشركة محل الدراسة. إن قيمة معامل الارتباط بين الأدوات الإحصائية لإدارة الجودة الشاملة وتخفيض التكاليف هي (0.936)، وهذا يدل على وجود درجة ارتباط قوية بين المتغيرين. وإلى أنَّ التغيرات الحاصلة من استخدام الأدوات الإحصائية لإدارة الجودة الشاملة تؤدي إلى تغير بنسبة (87.7%) في مجال استخدامها لتخفيض التكاليف في الشركة محل الدراسة. This research examines the role of total quality management tools, as an introduction to improve performance in the General Company for Cotton Yarn in Lattakia province. Where statistical tools, administrative and planning tools for TQM, and their role in improving performance were studied and the descriptive analytical method was adopted . It was the use of the link model and a simple model to study the relationship between two variables affiliated independent variable regression. The research has come to: The value of the correlation coefficient between the statistical tools to manage the overall quality and performance improvement is (0.949), and this indicates the presence of a strong degree of correlation between the two variables. And that the developments of the use of statistical tools for TQM lead to a change by (90.1%) in the field used to improve the performance of the company under study. The value of the correlation coefficient between the statistical tools to manage the overall quality and Reduce costs is (0.936), and this indicates the presence of a strong degree of correlation between the two variables. And that the changes of the use of administrative and planning tools for TQM lead to a change rate of (87.7%) in the field used to Reduce costs of the company under study.